A low-cost and effective seeding technique using protective core for restoration of Zostera marina habitats. Issue 3 (2nd July 2020) - Xie, Kun-Xiu; Li, Zheng; Li, Chao; Liu, Yan-Shan; Li, Wen-Tao; Zhang, Pei-Dong
Abstract : In this study, a protective seed core method for planting seeds of the common eelgrass Zostera marina was developed and evaluated through laboratory and field experiments. We studied the suitable desiccation period of the protective seed cores, and their effect on seed germination and seedling establishment in a laboratory experiment. New patches established by seeds planted with the protective seed cores were evaluated through an 11-month-seed-sowing field experiment. Observations of the stability of the protective seed cores and the change in viability of Z. marina seeds placed in the protective seed cores demonstrated that the optimum desiccation period was 2 days. Seed germination and seedling establishment of Z. marina were promoted by the protective seed cores during the 90-day laboratory experiment. The field experiment showed that the seedling establishment of Z. marina seeds was significantly enhanced by the protective cores, ranging from 12% to 64%, with an average of 30%, 6 months after seeding. New patches were successfully established by protective seed cores with a maximum shoot density of 367 shoots m −2 11 months after planting. The average planting cost per Z. marina seed was $0.03; thus, $14, 820 would be incurred for planting 1 ha of Z. marina beds using this method. These results indicate that the protective seed core method is an efficient and cost-effective restoration technique with a potential in facilitating large-scale restoration projects.